Charity On The Fringes Of The Medieval World: Skriðuklaustur, A Late Medieval Priory-Hospital In Eastern Iceland - Wood, Catharine M., 1971- (2013)
This is a study on the space and place of medieval monastic charity as represented by the infirmary that was in operation at Skriðuklaustur, a late medieval Augustinian monastery (1493-1554), located in eastern Iceland. In approaching the analysis on the space and place of care, the first step is to understand what was meant by medieval monastic hospitality and charity and the factors that differentiated between the two practices. This distinction between hospitality and charity as practiced by religious groups is important to understand because it dictated not only the form of interaction but also the location of interaction. Therefore, the second step in this study is identifying these places of care and how they were physically demarcated according to religious practice. This will be conducted by analyzing the location and architectural layout of monastic infirmaries and hospitals. Other material considerations in the practice of care include the artifacts associated with the medical profession as well as information from burials at monasteries and hospitals where the age, gender and types of pathological conditions that have been identified from the skeletal assemblage may reveal evidence of the practices and level of care administered at these infirmaries. The final step is the combination of the archaeological evidence and historical documentation that will be used to develop a context in which to understand how the social mechanisms of monasticism were used in the creation of space and place in the practice of charity towards secular society. This social aspect of monasticism played an integral role in developing and maintaining the monastic identity and it is through this understanding that the practice of charity may be recognized at the late medieval monastery, Skriðuklaustur.